CHARACTERISTIC SYMPTOMS OF Phytophthora palmivora ON COCOA LEAVES - Rina Sriwati; Rizky Muarif (Jurnal Natural, 2012)
The research was aimed to determine the characteristics symptoms of Phytophthora palmivora on cocoa leaves, and was conducted in Plant Diseases Laboratory, the Faculty of Agriculture Syiah Kuala University. Mature cacao leaves with almost the same size in the quotation were used at Lab. Plant disease. Suspensions of P. palmivora were inoculated on leaves by spraying techniques with several concentrations of treatment, 1x102, 1x104, 1x106. The results showed that cocoa leaves’ symptoms were getting yellow colour around the veins and the whole leaves eventually showed lesion on the third day after spraying. The higher spores’ population of P. palmivora could impact higher invasive infections. Characteristic symptoms will be very helpful in the process of observation of early disease in the nursery.